Aspects of the Development of Social Work as a Helping Profession - Kavaliauskienė, Vanda (Acta Paedagogica Vilnensia, 2005)
In different countries the profession of social work has “done its work" for more or less than a century. In Lithuania its history is revived and closely related to social transformation that has taken place after the restoration of independence in 1990. The question of how fully. if at all, social work has achieved professional status has been debated throughout the last century. It is known that efforts to evaluate whether social work is a „semi-profession" or a „fully developed profession” have been made by .l. Baird. Already in 1972 social work was considered as a profession. In the opinion of J. Baird to evaluate the status of the profession depends on whether social work is being measured by classical criteria of once „free" professions, or by contemporary criteria that are relevant to helping professions which are substantially committed to public and governmental service enterprise. The present picture of the professionalization of social work has changed. American social work's aspirations to professionalization is a natural process in a liberal market economy, because the profession is created and strengthened as a result of the personal interests of those earning a living by it. The status of social work as a profession is not unequivocally fixed. There are some aspects that are considered as negative to the professionalization of social work. Namely. the private practice of social work which is said has been growing dynamically since the middle of the 2th century. But with the dramatic rise of medical care, social workers are said to return to their original mission. The nature of professional practice in any particular stale is grounded in the historical and cultural context as mediated through political, economic and social systems. This makes social work difficult to define at the global level, and attempts to identify a universal essence of social work are problematic. Despite this apparent difficulty, there are some general definitions of social work.  Definitions provokc many questions. ls it possible to develop a universal definition of social work? If so, how well docs this definition describc social work throughout thc world? Does this definition apply to social work where l live? And the likc. At the beginning of the 21 st century, the European countrics have faced many problems of a diffcrent naturc. In ordcr to understand the nature of these problems an attempt is made to catcgorize them. Much is asked of social workers, and thcy are ones that are cxpccted to make a difference by empowering human beings to change sclf and socicty. The conclusion is that it is worthwhilc to explore, review social work as a profcssion becausc, according to Midgley, therc is a „need to dcvclop a broad intcrnational approach to the study of social work to generate a globai awareness that enhances the ability of social workers to transcend their preocupation with the local and contextualize their role within a globai setting"'.
Keywords: social work; profession; definition of social work; aid